Planning, management and administration of HS contents with BIM and VR in construction: an implementation protocol. Issue 2 (24th April 2020) - Getuli, Vito; Capone, Pietro; Bruttini, Alessandro
Abstract : Purpose: Building construction is considered a complex, dynamic and highly hazardous process, which embraces many factors that are potentially dangerous to workers. Many studies proved that the improvement of preventive and proactive measures – dynamically included in the building design, planning and construction – could reduce site accidents as well as increase the site productivity. In this context, process management models and information visualization techniques such as building information modeling (BIM) and virtual reality (VR) seem to be devoted to strongly contribute to the advancement of the current safety management practices. For these reasons, the presented contribution is based on the assumption that a more nuanced approach for construction worker's safety training is warranted and the authors propose a safety training protocol based on BIM-enabled VR activity simulations. Design/methodology/approach: The methodology comprised a safety training protocol based on BIM-enabled VR activity simulations. The protocol addresses three methodological issues: (1) Planning in terms of training typologies and related health and safety contents to be implemented in the VR construction site scenarios; (2) Management regarding the solution to integrate BIM and game technologies to deliver VR training experiences; (3) Administration in terms of definition of standardized rules to define a safety training schedule in a given construction project. Findings: This work contributes to provide a standardized protocol for a viable integration of BIM and VR technologies for construction safety training in real projects. Practical implications: The VR training protocol was applied to a construction project based in Italy that served as case study for the development of the training sessions' contents and their implementation. This case demonstrated the feasibility of the protocol's implementation and pointed out the drawbacks and limitations on which further efforts need to be spent in order to take the proposed protocol from a prototypical stage to a maturity for its larger-scale adoption from the practitioners involved in construction safety training. Originality/value: The research gives a contribution to reduce the currently existing knowledge gap regarding how BIM and VR can be simultaneously integrated in real projects for construction safety training by using standardized rules to be extensively reproduced in different construction projects. It uses a customized toolkit with a mobile smartphone solution to administer Safety Training Scenarios which increases its portability in construction site compared to PC-based VR solutions.